Who drive the health policy agenda in India? Actors in National Health Committees since Independence - Disha Agrawal; Parth Sharma; Vikash R. Keshri (Elsevier, 2024)
Introduction: Health policies reflect the ideas and interests of the actors involved. The Indian Government constituted many health committees for policy recommendations on myriad issues concerning public health, ranging from tribal health to drug regulation. However, little is known about their composition and backgrounds. We reviewed these committees to map the actors and institutions. Methods: We elicited information on all relevant health committees available in the public domain. All were constituted post-independence, except two, with recommendations that remain pertinent to date. Data for chairpersons and members - their professions, gender, institutions, and location were extracted and analysed. Reliable online sources were used to collate the information. Results: We identified 23 national health committees from 1943 to 2020 with available reports. There were 25 chairpersons and 316 members. All except three chairpersons were men. Among members, only 11% were women. The majority (51%) had experience working in health systems; however, most were medical doctors, with negligible representation of other cadres. We noted the centralization of location, with 44% of members based in the national capital of Delhi. Government administrators were maximally represented (55%), followed by medical academia (19%). Post-2000, we have observed slightly improved diversity across some parameters like gender (15% women vs 9% earlier) and affiliation. However, the centralization of the location to the national capital had increased (55% post-2000 vs. 39% pre-2000). Conclusion: Indian health committees lack diversity in representation from multiple perspectives. Henceforth, health policymakers should prioritize including diverse social, geographical, and health systems actors to ensure equitable policymaking.